KCNQ1 p.L353L affects splicing and modifies the phenotype in a founder population with long QT syndrome type 1. Issue 6 (6th March 2017) - Kapplinger, Jamie D; Erickson, Anders; Asuri, Sirisha; Tester, David J; McIntosh, Sarah; Kerr, Charles R; Morrison, Julie; Tang, Anthony; Sanatani, Shubhayan; Arbour, Laura; Ackerman, Michael J
Abstract : Background: Variable expressivity and incomplete penetrance between individuals with identical long QT syndrome (LQTS) causative mutations largely remain unexplained. Founder populations provide a unique opportunity to explore modifying genetic effects. We examined the role of a novel synonymous KCNQ1 p.L353L variant on the splicing of exon 8 and on heart rate corrected QT interval (QTc) in a population known to have a pathogenic LQTS type 1 (LQTS1) causative mutation, p.V205M, in KCNQ1 -encoded Kv7.1. Methods: 419 adults were genotyped for p.V205M, p.L353L and a previously described QTc modifier ( KCNH2- p.K897T). Adjusted linear regression determined the effect of each variant on QTc, alone and in combination. In addition, peripheral blood RNA was extracted from three controls and three p.L353L-positive individuals. The mutant transcript levels were assessed via qPCR and normalised to overall KCNQ1 transcript levels to assess the effect on splicing. Results: For women and men, respectively, p.L353L alone conferred a 10.0 (p=0.064) ms and 14.0 (p=0.014) ms increase in QTc and in men only a significant interaction effect in combination with the p.V205M (34.6 ms, p=0.003) resulting in a QTc of ∼500 ms. The mechanism of p.L353L's effect was attributed to approximately threefold increase in exon 8 exclusion resulting in ∼25% mutant transcripts of the total KCNQ1 transcript levels. Conclusions: Our results provide the first evidence that synonymous variants outside the canonical splice sites in KCNQ1 can alter splicing and clinically impact phenotype. Through this mechanism, we identified that p.L353L can precipitate QT prolongation by itself and produce a clinically relevant interactive effect in conjunction with other LQTS variants.